Increased endoplasmic reticulum stress in decidual tissue from pregnancies complicated by fetal growth restriction with and without pre-eclampsia - Lian, I.; Løset, M.; Mundal, S.; Fenstad, M.; Johnson, M.; Eide, I.; Bjørge, L.; Freed, K.; Moses, Eric; Austgulen, R. (2011)
Objectives: Endoplasmic reticulum (ER) stress has been implicated in both pre-eclampsia (PE) and fetal growth restriction (FGR), and is characterised by activation of three signalling branches: 1) PERK-pEIF2a, 2) ATF6 and 3) splicing of XBP1(U) into XBP1(S). To evaluate the contribution of ER stress in the pathogenesis of PE relative to FGR, we compared levels of ER stress markers in decidual tissue from pregnancies complicated by PE and/or FGR. Study design: Whole-genome transcriptional profiling was performed on decidual tissue from women with PE (n = 13), FGR (n = 9), PE+FGR (n = 24) and controls (n = 58), and used for pathway and targeted transcriptional analyses of ER stress markers. The expression and cellular localisation of ER stress markers was assesses by Western blot and immunofluorescence analyses. Results: Increased ER stress was observed in FGR and PE+FGR, including both the PERK-pEIF2a and ATF6 signalling branches, whereas ER stress was less evident in isolated PE. However, these cases demonstrated elevated levels of XBP1(U) protein. ATF6 and XBP1 immunoreactivity was detected in most (>80%) extravillous trophoblasts, decidual cells and macrophages. No difference in the proportion of immunopositive cells or staining pattern was observed between study groups. Conclusions: Increased PERK-pEIF2a and ATF6 signalling have been associated with decreased cellular proliferation and may contribute to the impaired placental growth characterising pregnancies with FGR and PE+FGR. XBP1(U) has been proposed as a negative regulator of ER stress, and increased levels in PE may reflect a protective mechanism against the detrimental effects of ER stress.